'Choosing shoes': a preliminary study into the challenges facing clinicians in assessing footwear for rheumatoid patients - Silvester, RN; Williams, AE; Dalbeth, N; Rome, K (Bio Med Central Ltd, 2010)
Background: Footwear has been accepted as a therapeutic intervention for the foot affected by rheumatoid arthritis (RA). Evidence relating to the objective assessment of footwear in patients with RA is limited. The aims of this study were to identify current footwear styles, footwear characteristics, and factors that influence footwear choice experienced by patients with RA. Methods: Eighty patients with RA were recruited from rheumatology clinics during the summer months. Clinical characteristics, global function, and foot impairment and disability measures were recorded. Current footwear, footwear characteristics and the factors associated with choice of footwear were identified. Suitability of footwear was recorded using pre-determined criteria for assessing footwear type, based on a previous study of foot pain. Results: The patients had longstanding RA with moderate-to severe disability and impairment. The foot and ankle assessment demonstrated a low-arch profile with both forefoot and rearfoot structural deformities. Over 50% of shoes worn by patients were open-type footwear. More than 70% of patients’ footwear was defined as being poor. Poor footwear characteristics such as heel rigidity and sole hardness were observed. Patients reported comfort (17%) and fit (14%) as important factors in choosing their own footwear. Only five percent (5%) of patients wore therapeutic footwear. Conclusions: The majority of patients with RA wear footwear that has been previously described as poor. Future work needs to aim to define and justify the specific features of footwear that may be of benefit to foot health for people with RA.